Characterization of Phenotypic Changes in Pseudomonas putida in Response to Surface-Associated Growth - Sauer, Karin (American Society for Microbiology, 2001)
The formation of complex bacterial communities known as biofilms begins with the interaction of planktonic cells with a surface. A switch between planktonic and sessile growth is believed to result in a phenotypic change in bacteria. In this study, a global analysis of physiological changes of the plant saprophyte Pseudomonas putida following 6 h of attachment to a silicone surface was carried out by analysis of protein profiles and by mRNA expression patterns. Two-dimensional (2-D) gel electrophoresis revealed 15 proteins that were up-regulated following bacterial adhesion and 30 proteins that were down-regulated. N-terminal sequence analyses of 11 of the down-regulated proteins identified a protein with homology to the ABC transporter, PotF; an outer membrane lipoprotein, NlpD; and five proteins that were homologous to proteins involved in amino acid metabolism. cDNA subtractive hybridization revealed 40 genes that were differentially expressed following initial attachment of P. putida. Twenty-eight of these genes had known homologs. As with the 2-D gel analysis, NlpD and genes involved in amino acid metabolism were identified by subtractive hybridization and found to be down-regulated following surface-associated growth. The gene for PotB was up-regulated, suggesting differential expression of ABC transporters following attachment to this surface. Other genes that showed differential regulation were structural components of flagella and type IV pili, as well as genes involved in polysaccharide biosynthesis. Immunoblot analysis of PilA and FliC confirmed the presence of flagella in planktonic cultures but not in 12- or 24-h biofilms. In contrast, PilA was observed in 12-h biofilms but not in planktonic culture. Recent evidence suggests that quorum sensing by bacterial homoserine lactones (HSLs) may play a regulatory role in biofilm development. To determine if similar protein profiles occurred during quorum sensing and during early biofilm formation, HSLs extracted from P. putida and pure C(12)-HSL were added to 6-h planktonic cultures of P. putida, and cell extracts were analyzed by 2-D gel profiles. Differential expression of 16 proteins was observed following addition of HSLs. One protein, PotF, was found to be down-regulated by both surface-associated growth and by HSL addition. The other 15 proteins did not correspond to proteins differentially expressed by surface-associated growth. The results presented here demonstrate that P. putida undergoes a global change in gene expression following initial attachment to a surface. Quorum sensing may play a role in the initial attachment process, but other sensory processes must also be involved in these phenotypic changes.